Synthesis, characterizations, antibacterial and photoluminescence studies of solution combustion-derived α-Al2O3 nanoparticles - Prashanth, P.A.; Raveendra, R.S.; Hari Krishna, R.; Ananda, S.; Bhagya, N.P.; Nagabhushana, B.M.; Lingaraju, K.; Raja Naika, H. (Journal of Asian Ceramic Societies, 2015)
In this work, we report a novel, economical, low temperature solution combustion synthesis (SCS) method to prepare α-Al2O3 (Corundum) nanoparticles. Powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HR-TEM), Fourier transform infrared spectroscopy (FT-IR), BET surface area and ultraviolet visible spectroscopy (UV–vis) measurements were used to characterize the product. Antibacterial studies were examined against gram −ve Klebsiella aerogenes, Escherichia coli, Pseudomonas desmolyticum and gram +ve Staphylococcus aureus bacteria by agar well diffusion method. The α-Al2O3 nanoparticles showed substantial effect on all the four bacterial strains. Photoluminescence (PL) measurements under excitation at about 255nm show that the alumina nanoparticles have emission peaks at 394 and 392nm.